The Influence of Digital Literacy and Product Innovation on the Competitive Advantage of Modern Beverage Businesses - Putri, Sylvia Octa; Abhista, Almer Devara; Achsan, Muhammad Ivan Firdaus; Sadiqa, Muthya (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study analyzes the transition of post-charismatic leadership in Central Asia region, focusing on Kazakhstan under President Kassym-Jomart Tokayev and Uzbekistan under President Shavkat Mirziyoyev. After periods of strong personal charisma exercised by the rulers of Nursultan Nazarbayev and Islam Karimov, both countries entered the stage of political adaptation when attempts were made to make the government system institutionalized without destabilizing the regime. By means of qualitative comparison and with the use of Max Weber’s notions of routinization of charismatic authority, the study analyzes the reformist trends and changes in the foreign policy priorities of both states. The outcomes of the study reveal that Uzbekistan is characterized by the presence of greater reformist trends and involvement in regional politics, whereas in Kazakhstan the processes of power consolidation can be observed in a more measured manner.